P-646 IVF outcomes of embryos with abnormal PGT-A biopsy previously refused transfer – a prospective cohort study. (30th June 2022) - Gleicher, N; Albertini, D; Molinari, E; Barad, D.H
Abstract: Study question: Will patients who have embryos diagnosed as abnormal by preimplantation genetic testing for aneuploidy (PGT-A) choose to have those embryos transferred after those embryos were refused transfer at other institutions and what are the potential clinical outcomes of those transfers? Summary answer: Many patients have selected embryos with PGT-A abnormal trophectoderm biopsies transferred since these embryos can still offer a chance of live birth. What is known already: PGT-A is a widely practiced method of selecting embryos for transfer based on biopsy of a few cells. Many clinical practices refuse to transfer PGT-A abnormal embryos even when there are no other "normal" embryos available. Study design, size, duration: This is a prospective cohort of 69 couples who, since 2014, moved a total of 444 PGT-A abnormal embryos previously refused transfer at their parent institutions to our practice. Among these, 50 patients have, thus far, undergone 57 transfer cycles of 141 embryos. Participants/materials, setting, methods: Embryos diagnosed at other institutions by PGT-A as abnormal (mostly using next generation sequencing) were moved to our academically affiliated private fertility and research center in New York City. Female age at retrieval was 41.35 ± 3.98 years, 74% were Caucasian, 12% Asian and 10% were of African descent. All embryos identified as PGT-A abnormal among prospectively identified couples were recorded in our center's registry. Main results and the role of chance: Among the 144 embryos transferred 102 (72.3%) had only 1 or 2 chromosomal abnormalities, 30 (21.3%) had 3 or more and 9 (6.4%) were "undiagnosed" because of degraded DNA, yet still had been refused transfer. Transfer of PGT-A abnormal embryos resulted in 8 live births, 11 miscarriages and no voluntary terminations. One child was born with a segmental duplication and required repair of coarctation of the aorta as a newborn. Many couples with only PGT-A abnormal embryos are willing to have their PGT-A abnormal embryos transferred and such transfers can result in establishment of ongoing euploid pregnancies and live births. Limitations, reasons for caution: Findings in this case series may not be representative of the wider population of couples undergoing IVF with PGT-A in general. Not all abnormal phenotypes present in the immediate postnatal period so it will be important to continue to follow the development of these children. Wider implications of the findings: PGT-A can result in a clinics refusal to transfer embryos with abnormal PGT-A biopsies, even those with mosaic findings, consequently large numbers of infertile women are prematurely advised that their only chance of motherhood is through third-party egg-donation. Trial registration number: Not applicable